I CALL MYSELF SNOB: POLITICS OF AESTHETICS OF KOREAN POETRY UNDER DICTATORSHIPS - HONG, Sunghee (International Journal of Korean Humanities and Social Sciences, 2017)
This study addresses the issue of politics of aesthetics in Korean poetry in regards of ‘authenticity of snobbism’ manifested in poems and essays published from late 1960s to 1980s under dictatorships. The special attention is on the double positioning of oneself as the accuser and the accused. The questions of the politics of aesthetics of Korean poetry, even the recent argument, has discriminated ‘authenticity’ from ‘snobbism’, in the needs to qualify literature as the accuser of the opportunism and passivism under the dictatorships. However, this dichotomy has restricted the political-aesthetic possibilities of literature to an exclusive property of poets or (poets as) ‘citizens’. This study explores how Korean poetry generated the possibility of political aesthetics from every single snobbish corner of lives by placing ‘the accuser’ of the dictatorial government on the position of ‘the accused’ through its own voice. Poems and essays of Kim Soo-young, Kim Kwang-kyu and Lee Seong-bok will be significantly examined as what manifested the autoimmunity of literature beyond the pose of self-reflection.